The Effectiveness of Brain-Based Learning with Think Pair Share Setting in Terms of Achievement, Representation Ability, and Anxiety of High School Students - Susilowati, Rina; Wutsqa, Dhoriva Urwatul (Universitas Islam Negeri Sunan Kudus, 2022)
Innovation in learning is needed by combining a learning approach and a classroom setting model to solve the problem of low student achievement and representation abilities. It can also be used as an effort to overcome problems in the aspect of attitude, for example, math anxiety. This study was aimed to (1) describe the effectiveness of the brain-based learning approach with a think pair share setting (BBL+TPS); (2) find out the difference between learning with BBL+TPS and the scientific approach; and (3) describe which one is more effective between the BBL+TPS and the scientific approach in terms of learning achievement, mathematical representation ability, and student’s math anxiety in statistics and probability. This study was a quasi-experimental study with the population being students of class X SMAN 2 Bantul, and the sample was students of classes X MIA 3 and X MIA 4, which were determined by using random sampling technique. The data collection techniques used are interviews, observations, and questionnaires. Data analysis techniques are descriptive and inferential statistics. The results show that: (1) BBL+TPS is effective; (2) there are differences in the effectiveness of learning between the BBL+TPS and the scientific approach; and (3) BBL+TPS is more effective than the scientific approach in terms of learning achievement and mathematical representation ability, but not more effective in terms of math anxiety. Diperlukan suatu inovasi dalam pembelajaran dengan menggabungkan pendekatan pembelajaran dan model pengaturan kelas untuk menyelesaikan permasalahan prestasi belajar dan kemampuan representasi siswa yang rendah. Hal tersebut juga dapat digunakan sebagai upaya untuk mengatasi permasalahan dalam aspek sikap contohnya kecemasan matematika. Penelitian ini bertujuan untuk (1) mendeskripsikan keefektifan pendekatan brain-based learning dengan setting think pair share (BBL+TPS), (2) mengetahui adanya perbedaan antara pembelajaran dengan pendekatan BBL+TPS dan saintifik, dan (3) mendeskripsikan mana yang lebih efektif antara pendekatan BBL+TPS dan saintifik ditinjau dari prestasi belajar, kemampuan representasi matematika, dan kecemasan matematika pada materi statistika dan peluang. Penelitian ini merupakan penelitian eksperimen semu dengan populasi adalah siswa kelas X SMA Negeri 2 Bantul dengan sampel penelitian adalah siswa kelas X MIA 3 dan X MIA 4, yang ditentukan dengan menggunakan teknik random sampling. Teknik pengumpulan data yang digunakan antara lain wawancara, observasi, dan angket. Teknik analisis data yaitu statistik deskriptif dan inferensial. Hasil penelitian menunjukkan bahwa: (1) pendekatan BBL+TPS efektif, (2) ada perbedaan keefektifan pembelajaran antara pendekatan BBL+TPS dan saintifik, dan (3) pendekatan BBL+TPS lebih efektif dibandingkan dengan pendekatan saintifik ditinjau dari pretasi belajar dan kemampuan representasi matematika, namun tidak lebih efektif ditinjau dari kecemasan matematika.